2017
DOI: 10.1111/emr.12277
|View full text |Cite
|
Sign up to set email alerts
|

Assisted natural regeneration accelerates recovery of highly disturbed rainforest

Abstract: Summary Large areas of rainforests in Australia and other tropical regions have been extensively cleared since the mid‐19th century. As abandoned agro‐pastoral land becomes increasingly prominent, there is an ongoing need to identify cost‐effective approaches to reinstate forest on these landscapes. Assisted regeneration is a potentially lower cost restoration approach which aims to accelerate forest recovery by removing barriers to natural regeneration. However, despite being widely used its ecological benefi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 33 publications
1
16
0
Order By: Relevance
“…Nevertheless, the lack of difference in outcomes of passive and active restoration in our study was consistent with these suggestions. Uebel et al (2017) found that ANR accelerated the early recovery of physical vegetation structure in the same study location as our study. However, we found no effect of differing age of ANR sites (1-3 versus 5-10 years) on the return of either decomposition rates or invertebrate decomposer communities.…”
Section: Recovery Of Decomposition Rates and Invertebrate Decomposerssupporting
confidence: 84%
See 2 more Smart Citations
“…Nevertheless, the lack of difference in outcomes of passive and active restoration in our study was consistent with these suggestions. Uebel et al (2017) found that ANR accelerated the early recovery of physical vegetation structure in the same study location as our study. However, we found no effect of differing age of ANR sites (1-3 versus 5-10 years) on the return of either decomposition rates or invertebrate decomposer communities.…”
Section: Recovery Of Decomposition Rates and Invertebrate Decomposerssupporting
confidence: 84%
“…At the time of the present study, the woody vegetation types were a mix of old‐growth forest (both rain forest and eucalypt forest) unmanaged successional (regrowth) vegetation, and areas of this regrowth which additionally had been targeted for assisted natural regeneration (ANR) during the previous decade, by the managers of the Numinbah Conservation Area. The unmanaged regrowth was characterized by relatively short trees and shrubs that provided a sparse canopy cover, with a high proportion of non‐native species, most notably the shrub Lantana camara (Uebel et al., ). The ANR interventions aimed to accelerate regeneration of native trees, mainly by suppressing L. camara and other non‐native plants using various cutting and herbicide applications, until seedlings and saplings of native trees had grown to close the canopy (Uebel et al., ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…On degraded sites, the basic principle of ANR is to protect and facilitate the growth of parent trees and regeneration [45]. In Australia, controlling non-native weeds and eliminating grazing has proved successful in regenerating highly disturbed rainforest [46]. Protecting roots and suckers also proved successful in rehabilitating slash-and-burn agricultural sites in the Democratic Republic of the Congo [47].…”
Section: The Implication Of These Results For Enrichment Planting As mentioning
confidence: 99%
“…Some authors highlight expensive costs associated with active restoration (Catteral and Harrison Catterall & Harrison, 2006), while others suggest that passive restoration is laden with unrecognised costs and only slowly reaches its objectives (Zahawi, Holl, & Reid, 2014). The debate is still ongoing, but Prach and del Moral (2015) suggest that criteria to choose between passive, intermediate (Uebel, Wilson, & Shoo, 2017) and active restoration may depend on the landscape. Yet, relatively few studies have simultaneously considered within site (i.e., local variables such as habitat, age, etc.)…”
mentioning
confidence: 99%